2016
DOI: 10.1016/j.chemosphere.2015.08.061
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation potential of a highly mercury resistant bacterial strain Sphingobium SA2 isolated from contaminated soil

Abstract: A mercury resistant bacterial strain, SA2, was isolated from soil contaminated with mercury. The 16S rRNA gene sequence of this isolate showed 99% sequence similarity to the genera Sphingobium and Sphingomonas of α-proteobacteria group. However, the isolate formed a distinct phyletic line with the genus Sphingobium suggesting the strain belongs to Sphingobium sp. Toxicity studies indicated resistance to high levels of mercury with estimated EC50 values 4.5 mg L(-1) and 44.15 mg L(-1) and MIC values 5.1 mg L(-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 33 publications
2
39
0
4
Order By: Relevance
“…The crystalline structures of deposited Hg were visualized by SEM. Sathyavathi et al (2013) and Mahbub et al (2016) have previously reported the SEM analysis of same crystalline structures of detoxified Hg.…”
Section: Discussionmentioning
confidence: 90%
“…The crystalline structures of deposited Hg were visualized by SEM. Sathyavathi et al (2013) and Mahbub et al (2016) have previously reported the SEM analysis of same crystalline structures of detoxified Hg.…”
Section: Discussionmentioning
confidence: 90%
“…De acuerdo al comportamiento observado, se evidencia un aumento en el crecimiento de microorganismos en suelo tratado, estos efectos se deben a la simbiosis que se produce entre las lombrices y los microorganismos del medio, tanto los que estaban en el suelo cuando se inició el proceso como las nuevas colonias registradas, evidenciándose una interacción lombrices-microorganismos [18,39].…”
Section: Resultados Y Discusiónunclassified
“…Minimal inhibitory concentration (MIC) for growth was measured for seven of the most tolerant strains in microtiter plates containing YNBG broth. Strains selected were Cryprococcus agrionensis CRUB 1310 T , Cryptococcus sp.…”
Section: Methodsmentioning
confidence: 99%